1984
DOI: 10.1192/bjp.144.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenic Patients and their Families a Survey in a Psychiatric service based on a DGH Unit

Abstract: We identified the population of schizophrenic patients under 65 in a geographically defined area. The number using psychiatric services based on a new District General Hospital unit in the course of one year was 364, a prevalence of 2.2 per 1000 adult population. Half the patients lived in supportive private households, most often with spouses or mothers. More women than men married and retained supporters. Patients and their primary supporters were interviewed separately. The PSE Catego programme classed 47 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
12

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 7 publications
8
119
1
12
Order By: Relevance
“…The mean (CSI) score were higher among nonemployed caregivers the absence of an effective health insurance to pay for patients medical expenses, as a result the entire burden of medical of the medical bills is borne by patients and their relatives, this finding are consistent with findings of (24,25,26,27) . In our study we found that caregiver burden is the highest in disorganized and catatonic types of schizophrenia and it is the lowest in residual type of schizophrenia, this finding is consistent with finding of (29,30,31) .…”
Section: Psychosocial Burden Among Caregivers Of Patients ………supporting
confidence: 82%
“…The mean (CSI) score were higher among nonemployed caregivers the absence of an effective health insurance to pay for patients medical expenses, as a result the entire burden of medical of the medical bills is borne by patients and their relatives, this finding are consistent with findings of (24,25,26,27) . In our study we found that caregiver burden is the highest in disorganized and catatonic types of schizophrenia and it is the lowest in residual type of schizophrenia, this finding is consistent with finding of (29,30,31) .…”
Section: Psychosocial Burden Among Caregivers Of Patients ………supporting
confidence: 82%
“…She also alluded to her frustration over Timothy's stubbornness, suggesting that he would not see 'anybody else's point of view' and also his alienation from the family: 'he came down to eat, he was totally silent, shoved his plate to one side and you couldn't communicate with him.' It has been suggested that such behaviour directed at carers may be very difficult to cope with (Gibbons et al, 1984;MacCarthy, 1988).…”
Section: Emotional Reactionsmentioning
confidence: 99%
“…Ces résultats sur la détresse psychologique contrastent avec ceux recensés dans les études précé-dentes, lesquelles rapportent des taux très élevés de détresse chez les proches de personnes présentant des problèmes graves de santé mentale (Provencher et al, 2003 ;Bibou-Nakou et al, 1997, Song et al, 1997Stengard et Stalokangas, 1997 ;St-Onge et Lavoie, 1997 ;Winefield et Harvey, 1993 ;Oldridge et Hugues, 1992 ;Gibbons et al, 1984) et une moins bonne qualité de vie (Addington et al, 2003 ;Hamada et al, 2003 ;Golimbet et Trubnikov, 2001 Tableau 3 Les prédicteurs de la détresse et de la qualité de vie identifiés par des analyses de régression multiples que la qualité des services reçus ait contribué à alléger leur détresse (Doornbos, 2002b ;Ostman et al, 2000 ;Lanzara et al, 1999 ;Greenberg et al, 1997). D'autre part, il est également possible que les personnes ayant des troubles mentaux graves qui ont été recrutées et qui ont accepté que leur famille soit interviewée, aient un niveau de fonctionnement supérieur à la moyenne et qu'elles aient de meilleures relations avec leur famille, allégeant ainsi leur fardeau et leur détresse.…”
Section: Discussionunclassified
“…D'autres études démontrent également que l'état de santé mentale des familles est souvent affecté par cette surcharge (Addington et al, 2003 ;Hirschfeld et al, 2003 ;Luscombe et al, 1998 ;Biegel et al, 1991 ;Pearlin et al, 1990 ;Zarit et al, 1985). La prévalence d'un niveau de détresse psychologique élevé varie de 25 à 40 % selon les études consultées (Bibou-Nakou et al, 1997 ;Song et al, 1997 ;Gibbons et al, 1984). Elle atteint même 60 % dans l'étude menée par Provencher et al (2003).…”
Section: éTat Des Connaissancesunclassified